Investigating students' awareness and conformity towards University dress code / Roslilee Ab. Halim, Mawarti Ashik Samsudin and Nurul Nadia Abd. Aziz - Ab. Halim, Roslilee; Ashik Samsudin, Mawarti; Abd. Aziz, Nurul Nadia (2012)
First impression is normally judged based on how a person is dressed. A person who appears with smart, clean and neat dress could portray a positive image and good qualities to the onlookers. Thus, the physical or outward appearance of students somehow reflects the students' inner values and eventually the image of the university. A preliminary survey conducted by researchers on 218 students revealed that more than 50 percent of them did not conform to the university dress code. In order to investigate the problem, researchers came out with this study which in specific aims to determine the level of students' awareness on university dress code and to identify factors contributing to the non-conformity of the dress code. Although the issues of dress code are not as much debated or studied as compared to students' achievements or academic issues in literatures, studies and researches should be undertaken so long the problem persists. Data for the study wasgathered through questionnaires from 146 UiTM students who did not conform to the university dress code. The data was then analyzedusing SPSS Version 20.0. The result showed that students are highly aware of the dress code policy and guidelines. However, despite their awareness, the majority of the students are found to disobey the dress code guidelines on most of the lecture days. Financial aspects are found to be the strongest factor among the four predictor factors in influencing dress code non-conformity. The findings are hoped to be beneficial to assist university administrators in handling the issue and implementing effective dress code policy.